European Yearbook of International Economic Law 2010 - Herrmann, Christoph; Terhechte, Jörg Philipp; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The first volume of the new Yearbook tries to catch the broadness of contemporary International Economic Law. In part I, it brings together articles on a variety of subjects, reaching from exchange rate manipulation and financial market supervision over international investment law including the growing investment protectionism to recent developments of the external economic constitution of the European Union and the relationship between climate change and International Economic Law. Part II covers the major regional economic integration developments around the globe, analysed in different articles covering the different regions. Part III informs about recent activities in some of the major global economic institutions.
Topics -- International Regulation and Supervision of Financial Markets After the Crisis -- Don Yuan: China’s “Selfish” Exchange Rate Policy and International Economic Law -- Protection of or Protection Against Foreign Investment? -- The Nascent International Law on Most-Favoured-Nation (MFN) Clauses in Bilateral Investment Treaties (BITs) -- Foreign Investment in Germany: Restrictions Based on Public Security Concerns and Their Compatibility with EU Law -- Going Global? The EU Common Commercial Policy After Lisbon -- Services Trade Liberalisation and Regulation: New Developments and Old Problems -- Applying European Competition Law to International Organizations: The Case of OPEC -- Mitigating Climate Change Through Price Instruments: An Overview of the Legal Issues in a World of Unequal Carbon Prices -- Regional Integration -- Regional Trade Agreements in the World Trade Order -- The European Union and Regional Trade Agreements -- Regional Economic Integration in the Middle East and North Africa: A Primer -- North American Regional Economic Integration: Recent Trends and Developments -- Integration in Latin America -- The ASEAN Economic Community Under the ASEAN Charter; Its External Economic Relations and Dispute Settlement Mechanisms -- International Economic Institutions -- The Doha Development Agenda at a Crossroads: What Are the Remaining Obstacles to the Conclusion of the Round? -- Recent Legal Developments in the International Monetary Fund -- The G8 and the Heiligendamm Process: A Group’s Architecture in Flux -- Book Reviews -- Jens-Christian Gaedtke, Politische Auftragsvergabe und Welthandelsrecht -- Markus Gehring, Nachhaltigkeit durch Verfahren im Welthandelsrecht. Umwelt- und Nachhaltigkeitsprüfungen und die WTO.
Keywords: International law; Trade; International economics; Political science; International Economic Law, Trade Law; International Economics; Political Science